Metatext as a cognitive-discursive mechanism of text organization and interpretation - Rakhmonov, Azizkhon Bositkhonovich (The Lingua Spectrum, 2026)
The article provides a theoretical and methodological substantiation of metatext as a cognitive-discursive mechanism for organizing and interpreting text. The relevance of the study is determined by the growing interest of contemporary linguistics and psycholinguistics in the procedural aspects of textual activity, including reflection, structuring, and interpretation management. The paper systematizes major approaches to defining metatext within text linguistics, cognitive discourse theory, and pedagogical communication. An original model of metatext is proposed, conceptualizing it as a multi-level structure comprising structural-organizing, reflexive, interpretative, and evaluative components. A functional typology of metatext is developed, encompassing cognitive, structuring, communicative, and metacognitive functions. The findings demonstrate that metatext acts as a cognitive navigator, reduces cognitive load, ensures discourse coherence, and regulates interpretative strategies of the addressee. Particular attention is paid to the functioning of metatext in pedagogical communication, where it serves as a tool for organizing instructional discourse and fostering learners’ metacognitive skills. The scientific novelty lies in the operationalization of the concept of metatext and the development of an analytical model applicable to the study of scientific and educational discourse.